The Role of Learning Media and Teacher Innovation on Student Interest in Sports Education - Gevan Naufal Wala (Siber International Journal of Sport Education, 2025)
Literature Review of the role of Learning Media and Teacher Innovation in increasing Student Interest is a scientific article with the aim of analyzing whether Student Interest plays a role in Learning Media and Teacher Innovation. The method examines various studies, articles, and books relevant to the topic discussed. The results of this article are: 1) Learning Media plays a role in Student Interest 2) Teacher Innovation plays a role in Student Interest. Apart from these 2 exogenous variables that influence the endogenous variable of Student Interest, there are still many other factors including motivation, learning facilities, family environment.